Insostenibilidad democrática. De la Sociedad del Riesgo a la Sociedad de la Turbulencia - Méndez Gallo, Pablo (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The planet is not infinite: according to a purely extractive model for social progress and economic growth, resources are almost over and the planet itself is nearly exhausted. Sustainability is presented as an intermediate remedy, in order to sustain the (unsustainable) economic model and to save the planet, at the same time – green capitalism. Useless, according to most predictions. The same thing happens in a political terrain: transformed the citizen into a mere commercial instrument, subjected to all kind of (social) outrages, in the interest of a sacrosanct political and economical model raised to the category of dogma, Democracy can not but surrender to the flows of those powers established on the fringes of governments, of the common interest. In this sense, Democracy, as a system for the organisation of the public life (community), ceases to be a shelter in order to become a desert. Materialization of risk, that is an actual turbulence, becomes an atmospheric phenomenon –climatic and political– characteristic of contemporary societies. Certainty is dead, and with it, community and democracy.
Keywords: Environment; Politics; Democracy; Sustainability; Risk society; Turbulence society